Current trends of resource saving in the dairy industry - Mykhalevych, Artur; Bandura (Kuzmyk), Uliana; Sapiga, Victoria (My University, 2022)
Resource savings at the enterprises of the dairy industry of Ukraine is a modern way to increase production efficiency and cost-effective implementation, which not only saves raw materials, but also affects the growth of production with the same quantities of whole milk, fuel and auxiliary materials. Milk and products of its processing are renewable raw materials, relatively expensive, and the process of their production - time-consuming. Therefore, in terms of full economic calculation, it is necessary to direct funds and efforts to preserve raw milk, to a more complete and rational use of all its components in the processing process.
Keywords: Dairy industry; resource saving; current trends; молочна промисловість; ресурсозбереження; сучасні тенденції; кафедра технології молока і молочних продуктів